Factors that influencing the muslims awareness towards writing a wasiah among Muslim in Klang Valley / Mohd Firdaus Amir and Nurizzati Sahak - Amir, Mohd Firdaus; Sahak, Nurizzati (Faculty of Business and Management, 2014)
Wasiah is an important legal document that empowers us to determine who benefits from ours assets. In new urban Malaysia, many are not aware that assets left by the dead are about billion unclaimed cash due to try to accumulate wealth but never considered making a wasiah. Therefore, the objectives of the study are to identify the relationship between family structures, individual characteristics and education levels with the factors that influence people to write a wasiah; and to analyze the most significant factors that influence Muslim awareness towards writing a wasiah. This research uses both primary and secondary data. A survey was carried out among 200 Muslim Malaysian in Klang Valley, Malaysia. The findings showed that these three factors that influencing the Muslim awareness towards writing a wasiah. In addition, the overall factors of Muslim awareness towards writing a wasiah also indicate that they are stimulated by the presentations of Muslim Malaysian itself. The data originally consists of dimension data analysis which includes descriptive, reliability test, Pearson correlation test and multiple regressions. The model will help to evaluate the factors that influencing the Muslim awareness in writing a wasiah and to find out the factors relationship and significant of Muslim awareness in writing a wasiah.